The Emotional Expressions of Chinese People in Batam Island - Wilis Srisayekti; Jeany Hesty Buana (ANIMA Indonesian Psychological Journal, 2014)
Chinese people have long been a subject in the social history in Indonesia and their emotional expressions in front of the public especially have been affected by history. The previous empirical research findings in the Batam Island showed that Chinese people had unique emotional expression and this uniqueness may inflict interpersonal conflict with people of other ethnicities. This research was held to describe the emotional expression of the Chinese in the Batam Island. Their expressions compared with those of non Chinese. The adapted Display Rules Assessment Inventory (Matsumoto & Yoo, 2007) were distributed to the research participants (men and women in the Batam Island, totally 195 Chinese and 132 non Chinese). The analysis data result were presented in percentage and it showed that there were several similarities and differences between these two ethnic groups on (1) the display rules of seven basic emotions and (2) the display rules of emotion toward targeted persons, both in public and in private places. Based on the socioculutral paradigm, this finding will help solve any interpersonal – related problems faced by the Chinese with people of other ethnicities in the Batam Island.